Superiority of a Novel Mp1p Antigen Detection Enzyme Immunoassay Compared to Standard BACTEC Blood Culture in the Diagnosis of Talaromycosis. (21st June 2020) - Thu, Nguyen T M; Chan, Jasper F W; Ly, Vo Trieu; Ngo, Hoa T; Hien, Ha T A; Lan, Nguyen P H; Chau, Nguyen V V; Cai, Jian-Piao; Woo, Patrick C Y; Day, Jeremy N; van Doorn, Rogier; Thwaites, Guy; et al.
Abstract: Background: Talaromycosis is an invasive mycosis endemic in Southeast Asia and causes substantial morbidity and mortality in individuals with advanced human immunodeficiency virus (HIV) disease. Current diagnosis relies on isolating Talaromyces marneffei in cultures, which takes up to 14 days and is detectable only during late-stage infection, leading to high mortality. Methods: In this retrospective case-control study, we assessed the accuracy of a novel Mp1p antigen-detecting enzyme immunoassay (EIA) in stored plasma samples of 372 patients who had culture-proven talaromycosis from blood or sterile body fluids (reference standard) and 517 individuals without talaromycosis (338 healthy volunteers; 179 with other infections). All participants were recruited between 2011 and 2017 in Vietnam. Results: Of cases and controls, 66.1% and 75.4%, respectively, were male; the median age was 33 and 37, respectively. All cases were HIV infected; median CD4 count was 10 cells/μL. At an optical density cutoff of 0.5, the specificity was 98.1% (95% CI, 96.3%–99.0%); the sensitivity was superior to blood culture (86.3% [95% CI, 82.3%–89.5%] vs 72.8% [95% CI, 68.0%–77.2%]) ( P < .001, McNemar test). The time to diagnosis was 6 hours vs 6.6 ± 3.0 days for blood culture. Paired plasma and urine testing in the same patients (n = 269) significantly increased sensitivity compared to testing plasma alone or testing urine alone ( P < .001 and P = .02, respectively, McNemar test). Conclusions: The Mp1p EIA is highly specific and is superior in sensitivity and time to diagnosis compared to blood culture for the diagnosis of talaromycosis. Paired plasma and urine testing further increases sensitivity, introducing a new tool for rapid diagnosis, enabling early treatment and potentially reducing mortality. Abstract : The novel Mp1p enzyme immunoassay is superior in sensitivity compared to standard BACTEC blood culture and substantially shortens time to diagnosis of talaromycosis. This is a novel non-culture-based tool for rapid diagnosis, enabling early treatment and potentially reducing mortality.